Reimagining the Meaning of Learning: The Relevance of Educational Philosophy in the Face of the Onslaught of Digital Technology - Bagas Agamy Bakti; Muhammad Suma Hafiz; Herlini Puspika Sari (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to formulate a theoretical model on the relevance and strategic role of the philosophy of education in redefining the meaning of learning amid the dominance of digital technology. The central issue is how the philosophy of education can offer a robust conceptual framework to navigate, not merely utilize, the digital ecosystem. This research employs a qualitative approach using the Library Research method, focusing on philosophical-conceptual analysis.The findings indicate that technology triggers a shift in the meaning of learning from a one-way transfer of information to the active construction of knowledge (constructivism), transforming the teacher into a critical facilitator. The core relevance of philosophy (Axiology, Epistemology, Ontology) is heightened. Epistemology serves as a fortress against the "Digital Truth Crisis" by demanding critical literacy, while Axiology provides a moral compass for digital ethics issues. In synthesis, the enriched meaning of learning is a metacognitive process that merges technical proficiency with moral maturity (wisdom). The philosophy of education acts as a moral and intellectual regulator, ensuring that technology serves the ultimate goal of education: the holistic development of human beings.